VALUE-SENSE AXES IN THE FORMATION, DEVELOPMENT AND TRANSFER OF THE STRATEGIC CULTURE OF THE PEOPLE - Shedyakov, Vladimir (Collection of scientific papers «ΛΌГOΣ», 2023)
Value-sense axes of biosocial organisms: different levels - affect the formation and correction of the transformation orbits of the participants in the transformations [1-5]. To strategy is a necessity for optimizing the ways, forms and stages of transformation. Value-sense complexes constitute a defining element of both socialization and, in particular, the mechanism for the formation, transmission and development of the strategic culture of the people. Decision making adaptability includes feedback mediation. Reflective exploration of possible courses of action calculates the prospects for individual and team action. The derivation of the characteristics of the grey everyday life of dull everyday life to the depth of sacred meaning allows us to translate the analysis into the plane of value factors of transformations. Creativity as a way of life harmony with oneself and the world is based on the embodiment of basic value-sense complexes. Reflection becomes the foundation of creative search actions and exploratory behaviour with an analysis of the potential of both probabilistic, calculated, and intuitive, unconscious elements of choice. The specificity of the hierarchies of value-sense complexes leaves an imprint on ideas about the harmony of life, ways of creative development of the world [6-10]. Ideas about the normative and fair leave their mark on strategic preferences. In particular, the separation of aid from neo-colonialism and neo-mercantilism runs along the same watershed as the divergence of the development course from being pumped out, depleted by political, economic and/or military-administrative and cultural-ideological mechanisms. Are the conditions for the life and creativity of the people improving, or are the channels for exporting raw materials and exploiting the potential being improved? How do the direction and pace of change compare in the centre and on the periphery, in the metropolis and the colony? Are conflicts considered as a possible source of increased controllability, quenched or fomented? As you know, the colonialists not only sought to pump out all the wealth, but also drastically worsened the life of the natives (even if they did not kill immediately), which, from quite tolerable, organically corresponding to the conditions, instantly became unbearable. Often - it turned from almost heavenly into almost the embodiment of hell on earth. Compulsion to truly hard labour was carried out both by economic (cutting off alternative opportunities for obtaining means of subsistence) and by non-economic measures of influence. And the current wave of neo-colonial expansionism (first of all, enterprises-"factories" of the military-industrial complex and pumping out natural resources) also includes measures of economic and non-economic coercion to work on them, including those based on a break with traditional ideas about moral, fair, organically developed. It is obvious that the right to profess one's native religion, to use one's native language, to create in the forms of native culture are inalienable, as, for example, the right to life and prosperity.